The Role of Motivational Climate and Career Development as Determinants of Job Performance among Primary Health Care Workers - Muchti Yuda Pratama; Fitriani Pramita Gurning; Suharto Suharto; Fakhrurradhi Luthfi; Irwansyah Lubis; Nirma Juli Saputri; Roni Gunawan; Benri Situmorang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
The quality of primary health care services is greatly influenced by the performance of health workers. Service quality and organizational effectiveness are supported by good employee performance. However, employee performance can be affected by increasing workload and limited organizational resources. Only limited empirical evidence has been provided on the roles of motivational climate and career development in improving job performance among primary health care workers, especially in Indonesia. This study was conducted to examine the effects of motivational climate and career development on the job performance of health workers in community health centers. A cross-sectional quantitative design was employed involving 350 health professionals from 18 community health centers in Dairi Regency, North Sumatra, Indonesia. Data were collected by using structured questionnaires. After the classical assumption tests were completed, the data were analyzed by using multiple linear regression. The findings indicate that both motivational climate and career development have positive and significant effects on job performance (p<0.001). Career development emerged as the strongest predictor (β=0.566), followed by motivational climate (β=0.279). It was found that 64.4% of the variance in job performance was explained by the regression model. Strong explanatory power was shown by the model. It is shown by these findings that stronger career development systems and a supportive motivational climate should be developed. These are considered important strategies for improving the performance of health workers in primary health care settings. Keywords: Motivational Climate, Career Development, Job Performance,  Primary Health Care, Workers